Македонско спиновање Бориса - Донев, Дејан (Завод за проучавање културног развитка, Београд, 2013)
The issue of PR impact on the editorial policy of the media is the same as the question “What is older: the egg or the chicken?”, especially in the subject region and in terms of transformation from “snatch privatisations”, through transition and “buddy capitalism” towards embracing neoliberal economic spirit and (quasi)democracy. All of this is reviewed from the aspect of what has been happening in the Republic of Macedonia lately. On the one hand, we have the violent attempt of Macedonian Government to force through their media spokespersons passing of the Media Act as eligible, Euro-desirable and highly imperative, while on the other hand the Macedonian Association of Journalists use their last diffused efforts to try to promote and implement the idea of self-regulation of the media. In such circumstances, when PR not only obviously, but also forcefully influence the editorial policies of the media, the victim is not only the public itself but also, on the short run, the PR practitioners themselves. This raises the question of whether the PR business has its own professional ethics and should PR practitioners uphold it, or serve as a spinning tool like in the example of “spinning Boris”?
Macedonian spinning of Boris
Keywords: spinning, media, public, PR ethics